2017
DOI: 10.1002/cbic.201700221
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Tools for Facilitative Carbohydrate Transporters (Gluts)

Abstract: Facilitative carbohydrate transporters-Gluts-have received wide attention over decades due to their essential role in nutrient uptake and links with various metabolic disorders, including diabetes, obesity, and cancer. Endeavors directed towards understanding the mechanisms of Glut-mediated nutrient uptake have resulted in a multidisciplinary research field spanning protein chemistry, chemical biology, organic synthesis, crystallography, and biomolecular modeling. Gluts became attractive targets for cancer res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 111 publications
0
19
0
1
Order By: Relevance
“…It is also demonstrated that insulin/AKT signalling pathway mediates the impact of JAZF1 on hepatic gluconeogenic gene expression . Under IR state, the absorption of glucose in the insulin‐targeting organ is attenuated due to decreased Glucose transporter protein (GLUTs) expression . Both animal studies and in vitro studies reported that JAZF1 up‐regulated the mRNA expression of GLUT2 expression in the liver, which is the major glucose transporter of hepatocyte .…”
Section: The Potential Roles Of Jazf1 On Treatment Of T2dmmentioning
confidence: 99%
“…It is also demonstrated that insulin/AKT signalling pathway mediates the impact of JAZF1 on hepatic gluconeogenic gene expression . Under IR state, the absorption of glucose in the insulin‐targeting organ is attenuated due to decreased Glucose transporter protein (GLUTs) expression . Both animal studies and in vitro studies reported that JAZF1 up‐regulated the mRNA expression of GLUT2 expression in the liver, which is the major glucose transporter of hepatocyte .…”
Section: The Potential Roles Of Jazf1 On Treatment Of T2dmmentioning
confidence: 99%
“…One of the strategies developed for delivering anticancer drugs is the use of glucose transporting proteins [ 6 , 7 ]. Compared to healthy cells, rapidly proliferating cancer cells have a different energy metabolism, characterized by a high rate of glycolysis process, known as the Warburg effect [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Glucose and its derivatives get into the cell mainly through GLUTs (Glucose Transporters), membrane proteins facilitating the glucose transport across the cell membrane [30,31]. Sugar-drug conjugates are extensively used in cell imaging and drug delivery systems based on monosaccharide transport proteins [10,15,16,31]. Main requirements for the efficient uptake of the conjugates are as small as possible size of the aglycone and the absence of permanently charged groups [26,32].…”
Section: Introductionmentioning
confidence: 99%